Financial Constraints, Cash Holdings and Investment Behaviours: An Empirical Investigation of US Manufacturing Industry - CHEN, YIDAN (2017)
Financial constraints are important to firms’ cash holdings and investment activities. This article aims to estimate the relationships between financial constraints and the level of cash holdings and the relation between financial constraints and the degree of firms’ investment behaviours. Firms in US manufacturing industry are sampled during 2008 to 2016. Four models are conducted, which are the baseline model of cash flow sensitivity of cash, the robustness model of cash flow sensitivity of cash, the baseline model of investment cash flow sensitivity and the robustness model of investment cash flow sensitivity. Three criteria are used to differentiate firms, which are dividend pay-out ratio, firm size and KZ index. Using a series of tests, such as correlation test, White Test and Hausman Test, I conclude that constrained firms have more propensity on cash retention from cash flows and are more likely to reserve cash from the cash flow for the future investments. Additionally, the status of financial constraints can influence firms’ investment behaviours. Finally, the relationship between cash flows and investment is unsigned.